ON SYNERGETICS AS AN INTERDISCIPLINARY AREA OF SCIENTIFIC RESEARCH - Abullaeva Barno Hatamovna (Zeta Repository, 2023)
The article deals with synergetics as an independent direction and its connection with other sciences; integrative or synthetic value of synergetics; the role of research carried out in this area of scientific activity